Harmothoe hyalonemae sp. nov. (Polychaeta, Polynoidae), an exclusive inhabitant of different Atlanto-Mediterranean species of Hyalonema (Porifera, Hexactinellida). - Martin, D.; Rosell, D.; Uriz, M.J. (Ophelia, 1992)
A new polynoid species, Harmothoe hyalonemae, living as an inquiline inside the atrial cavities of deep-water hexactinellid sponges of the genus Hyalonema - viz. H. thomsoni; H. infundibulum, H. lusitanicum and H. toxeras - is fully described and illustrated. It is characterized by the notched, billshaped tips of neurosetae, smooth cephalic sensory organs and cirri, and smooth margined elytra with a patch of papillae near the reniform indentation. The species shows sexual dimorphism and the morphology of the polychaetes changes slightly when comparing specimens from Mediterranean hosts to those of Atlantic hosts. Some trends of the association between the polychaete and the sponge have been studied on a dense population of Mediterranean H. thomsoni (including 171 of the total 176 hexactinellid specimens examined). 88.3% of the sponges were infested by the polychaete, with 52.3 % of them harbouring a male and female together. The absence of correlation between sponge size and polychaete size, together with their particular distributions in size-classes ( normal unimodal in sponges, and bimodal in polychaetes ), suggest that the life-history of the polychaete population is independent of the host, with sponge life being notably longer than inquiline life.
Kristian Fauchald's Polychaeta DB